Towards a clinical pathway to food for special medical purpose in China: current progress based on a cross-sectional survey - Gong, Jie; Wang, Mengyan; Guo, Jiankui; Lyu, Yishu; Mu, Dongyu; Shi, Lei; Hu, Wen; Yu, Fengmei (Frontiers in Medicine, 2025)
Background and objectivesTo investigate the current status of clinical pathway implementation for food for special medical purpose (FSMP) in China and provide a scientific basis for constructing a standardized pathway.Methods and study designAn E-questionnaire was distributed to 27 clinical nutrition quality control centers in tertiary medical institutions in China from September to October 2023 via random stratified sampling.ResultsNinety-eight valid questionnaires were ultimately recovered. The number of FSMPs used ranged from 1 to 33. The rates of active nutritional risk screening, nutritional status assessment and diagnosis before FSMP therapy were 93.87, 93.88, and 97.96%, respectively. In addition to nutritional physicians, dietitians, and clinicians, nurses participated in prescribing FSMP in 12.24% of the hospitals. Before a prescription was issued, 65 (66.33%) hospitals had an audit process conducted by superior clinicians or dietitians. The frequency of routine ward rounds for more than half of the hospitalized inpatients was once a day. Post-discharge follow-up was implemented in 57 (58.16%) hospitals. The preparation of FSMP in 77 (87.50%) hospitals was included in the supervision of nosocomial infection. The frequency of infection supervision in half of the hospitals was once a month. Sixty-four (65.31%) hospitals had established monitoring and treatment plans for FSMP adverse reactions. Eighteen (18.37%) hospitals had set up FSMP counters for patients. Outpatients from 79 (80.61%) hospitals received FSMP in the department of clinical nutrition. Forty-five (45.92%) hospitals had charge codes. More than 20 different types of charges were collected.ConclusionAn FSMP clinical pathway prototype (Nutritional Screening-Assessment-Diagnosis-Treatment) has been implemented in China’s tertiary medical institutions. However, many irregularities exist. A standardized clinical pathway with universality and enforceability needs to be developed and promoted. There is an urgent need for China to strengthen its regulation policies and for other countries to share their experiences in the clinical application of FSMP.